Perlindungan Hukum terhadap Hak Asasi Manusia Terkait Penempatan Transpuan dalam Sel Tahanan - Alfi Syahrin Rahazade, Raden Roro Hanny; Yunanto, Yunanto (LPPM Universitas Ekasakti Padang, 2024)
Every human being has human rights which are inherent from birth, including transwomen. Human rights are considered as fundamental rights whose protection is guaranteed by the state. The aim of this study is to know and study the position of transwomen according to law in Indonesia and the legal protection of human rights in terms of prison placement for transwomen prisoners. Furthermore, the study used normative juridical methods by analyzing library materials obtained through library research. The results of the research show that transwomen as a group of society are vulnerable to discrimination due to inappropriate prison placement. The absence of regulations governing the placement of transwomen in appropriate prison taking into account their dignity and worth has given rise to doubts among law enforcement officials in imposing sentences. In addition, placing transwomen prisoners in special detention cells is the right step in order to provide a fair and correct legal solution for transwomen.